Assessing environmental drivers of vegetation health using enhanced vegetation index and principal component analysis: a case study of the Cradle Nature Reserve, Gauteng province, South Africa - Charles Matyukira; Paidamwoyo Mhangara; Eskinder Gidey; Jaabir Hussein (Geocarto International)
Protected environments, such as the Cradle Nature Reserve, are susceptible to environmental factors, including rainfall, temperature, and soil moisture, which affect vegetation health and productivity. This study explores vegetation growth dynamics using Enhanced Vegetation Index (EVI) time series derived from Sentinel-2 imagery from 2019 to 2023. Principal Component Analysis (PCA) was applied to reduce data dimensionality and extract the most influential environmental variables. The analysis identified two dominant components: Factor 1 (F1), strongly associated with rainfall and soil moisture, which explained 72.12% of the variance, and Factor 2 (F2), linked to temperature, accounting for an additional 17.96%. Water availability emerged as the primary determinant of vegetation vigor, while temperature played a secondary but critical role by increasing evapotranspiration rates and intensifying vegetation stress during dry seasons. Seasonal stress responses were captured by examining EVI variations across wet and dry periods, revealing vegetation’s sensitivity to both moisture presence and thermal extremes.